2017
DOI: 10.23986/afsci.60443
|View full text |Cite
|
Sign up to set email alerts
|

Recycling nutrients from horse manure: effects of bedding type and its compostability

Abstract: Manure constitutes a nutrient resource that should be efficiently recycled in agriculture. We assessed the nutrient cycling properties of three bedding materials (peat, wood shavings and pelleted straw) in horse manure by comparing their compostability, ability to retain nitrogen (N) and phosphorus (P) under rainfall and capacity to release N when mixed with soil. Manure with pelleted straw bedding had superior composting characteristics as it lost half of its dry mass, reached temperatures >60 °C and ended up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
(52 reference statements)
2
15
0
Order By: Relevance
“…The DM disappearance averaged 50% across all treatments (p > 0.10; Table 2). A comparable 50% DM loss has also been reported in other studies composting equine manure and pelleted straw [3,6].…”
Section: Gas Production and Dry Matter Disappearancesupporting
confidence: 86%
See 2 more Smart Citations
“…The DM disappearance averaged 50% across all treatments (p > 0.10; Table 2). A comparable 50% DM loss has also been reported in other studies composting equine manure and pelleted straw [3,6].…”
Section: Gas Production and Dry Matter Disappearancesupporting
confidence: 86%
“…Briefly, feces from horses supplemented with trace minerals (ING and ORG) had significantly greater concentrations of Cu and Zn, and tended to have greater concentrations of Co compared to CON [18]. Other studies have also reported an increase in mineral concentration after composting [6]. Despite greater concentrations of minerals in compost, these minerals have been shown to be more stable and less water soluble [6].…”
Section: Mineral Content Of Compostmentioning
confidence: 99%
See 1 more Smart Citation
“…Total P was analyzed spectrometrically (ICP-OES, Thermo Jarrel Ash Iris advantage, Franklin, MA, USA). The proportion of soluble P (phospahte-P, PO 4 -P) was analyzed from 1:60 water extracts using a continuous photometric flow analyzer (Aquakem 250, Thermo Fisher Scientific Inc., Vantaa, Finland) as described by Keskinen et al [31]. Because only a very low proportion (about 1%) of the phosphorus is excreted in the urine [8,10,12], urine was not collected in this experiment.…”
Section: Feces Sampling and Analysismentioning
confidence: 99%
“…There may also be economic motives to catch the P in feces and absorb it in bedding materials, because the use of horse manure may reduce fertilizing costs. When horse manure is composted, its nutrients can be recycled and utilized [31], which reduces the use of inorganic fertilizers.…”
Section: Impact Of Horse Diets On P Leachingmentioning
confidence: 99%